A massively parallel reporter assay reveals context-dependent activity of homeodomain binding sites in vivo - Hughes, Andrew E.O.; Myers, Connie A.; Corbo, Joseph C. (Genome Research, 2018)
Cone-rod homeobox (CRX) is a paired-like homeodomain transcription factor (TF) and a master regulator of photoreceptor development in vertebrates. The in vitro DNA binding preferences of CRX have been described in detail, but the degree to which in vitro binding affinity is correlated with in vivo enhancer activity is not known. In addition, paired-class homeodomain TFs can bind DNA cooperatively as both homodimers and heterodimers at inverted TAAT half-sites separated by 2 or 3 nucleotides. This dimeric configuration is thought to mediate target specificity, but whether monomeric and dimeric sites encode distinct levels of activity is not known. Here, we used a massively parallel reporter assay to determine how local sequence context shapes the regulatory activity of CRX binding sites in mouse photoreceptors. We assayed inactivating mutations in more than 1700 TF binding sites and found that dimeric CRX binding sites act as stronger enhancers than monomeric CRX binding sites. Furthermore, the activity of dimeric half-sites is cooperative, dependent on a strict 3-bp spacing, and tuned by the identity of the spacer nucleotides. Saturating single-nucleotide mutagenesis of 195 CRX binding sites showed that, on average, changes in TF binding site affinity are correlated with changes in regulatory activity, but this relationship is obscured when considering mutations across multiple cis-regulatory elements (CREs). Taken together, these results demonstrate that the activity of CRX binding sites is highly dependent on sequence context, providing insight into photoreceptor gene regulation and illustrating functional principles of homeodomain binding sites that may be conserved in other cell types.